2010
DOI: 10.1007/s00213-010-1775-1
|View full text |Cite
|
Sign up to set email alerts
|

Neurokinin-1 receptors (NK1R:s), alcohol consumption, and alcohol reward in mice

Abstract: Acute blockade of NK1R:s mimics the effects of NKR1 gene deletion on alcohol consumption, supporting a direct rather than developmental role of the receptor in regulation of alcohol intake. Inactivation of NK1R:s critically modulates alcohol reward and escalation, two key characteristics of addiction. These data provide critical support for NK1R antagonism as a candidate mechanism for treatment of alcoholism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 55 publications
1
59
3
Order By: Relevance
“…For example, NK1R À / À mice consume less alcohol in a two-bottle free-choice paradigm, and do not exhibit alcohol CPP (George et al, 2008;Thorsell et al, 2010). The decreased alcohol consumption and reward found in NK1R-null mutants is unlikely to be the result of compensatory developmental processes caused by constitutive gene deletion because these behavioral effects were replicated by NK1R antagonist administration in wildtype animals (Thorsell et al, 2010). Taken together, these observations have provided support for the hypothesis that NK1R antagonism may have utility as a pharmacotherapy for alcoholism.…”
Section: Introductionmentioning
confidence: 99%
“…For example, NK1R À / À mice consume less alcohol in a two-bottle free-choice paradigm, and do not exhibit alcohol CPP (George et al, 2008;Thorsell et al, 2010). The decreased alcohol consumption and reward found in NK1R-null mutants is unlikely to be the result of compensatory developmental processes caused by constitutive gene deletion because these behavioral effects were replicated by NK1R antagonist administration in wildtype animals (Thorsell et al, 2010). Taken together, these observations have provided support for the hypothesis that NK1R antagonism may have utility as a pharmacotherapy for alcoholism.…”
Section: Introductionmentioning
confidence: 99%
“…Also, these animals consume less alcohol in voluntary two-bottle choice drinking over a range of pharmacologically active concentrations (George et al, 2008). Decreased alcohol consumption in NK1R 2/2 mice was replicated by NK1R antagonist administration in wildtype C57/BL6 mice (Thorsell et al, 2010). In this study, there appeared to be an interaction between genotype and NK1R antagonist efficacy, with wild-type mice responding to lower doses of the antagonist than heterozygotes.…”
Section: Preclinical Findings In Rodent Models Of Drug Addictionmentioning
confidence: 53%
“…Thus, both pharmacologic blockade of NK1Rs and transient knock-down of their expression mimic the effects of constitutive NK1R gene inactivation. Thorsell et al (2010) further demonstrated that NK1R 2/2 mice do not escalate their voluntary alcohol consumption after repeated cycles of deprivation, suggesting that the SP/NK1R system may be involved in neuroadaptations that influence the development of escalated alcohol seeking.…”
Section: Preclinical Findings In Rodent Models Of Drug Addictionmentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, in healthy young men infusion of SP caused an anxiogenic and memorydisturbing effect (Herpfer et al 2007). On the other hand, mice genetically deficient in NK1R displayed suppressed alcohol consumption (George et al 2008;Thorsell et al 2010) and disrupted behaviors associated with morphine reward (Gadd et al 2003). Furthermore, systemic application of an NK1R antagonist into mice with high anxiety-related behavior as well as microinjection of an NK1R antagonist into the amygdala of gerbils caused anxiolytic-like effects (Heldt et al 2009;Sartori et al 2011).…”
Section: Possible Synaptic Network Correlates and Functional Significmentioning
confidence: 99%